In sickness and in health? Health shocks and relationship breakdown: Empirical evidence from Germany - Christian Bünnings; Lucas Hafner; Simon Reif; Harald Tauchmann (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
From an economic perspective, marriage and long-term partnership can be seen as a riskpooling device. This informal insurance contract is, however, not fully enforceable. Each partner is free to leave when his or her support is needed in case of an adverse life event. An adverse health shock is a prominent example for such events. Since relationship breakdown itself is an extremely stressful experience, partnership may backfire as informal insurance against health risks, if health shocks increase the likelihood of relationship breakdown. We address this question empirically, using survey data from Germany. Results from various matching estimators indicate that adverse shocks to mental health substantially increase the probability of a couple splitting up over the following two years. In contrast, there is little effect of a sharp decrease in physical health on relationship stability. If at all, physical health shocks that hit both partners simultaneously stabilize a relationship.
Keywords: I12; J12; D13; 330; separation; partnership dissolution; health shock; MCS; PCS; matching